Sociolinguistics for university postgraduate studies: approach - Ali, Asem Shehadeh Saleh; Yeob, Shamsul Jamili (2017)
The course exposes the relations between linguistic phenomena and social phenomena and their importance in the construction of human language. The language is influenced by customs, traditions and social order in a time and place designated since the language and social life is found. The language is closely linked to the community and each property of language initiated by society. The teaching of Arabic Language takes advantage of sociolinguistics in the sense that it provides a method of teaching and learning based on the life of the community in the same language.